2010
DOI: 10.1002/pssb.201046098
|View full text |Cite
|
Sign up to set email alerts
|

Structural stabilities and electronic and elastic properties of CdO: A first-principles study

Abstract: The structural phase transition and electronic and elastic properties of CdO have been studied by first-principles pseudopotential calculations. Seven possible potential structures have been considered and our calculations show that there exists a structural phase transition from the NaCl-type (B1) structure to the CsCl-type (B2) structure above 86.6 GPa. The moderately high bulk modulus might partially originate from the strong Cd 5s-O 2p hybridization. The variations of elastic constants (C ij ) with pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…It is found that the static phase transition from the rocksalt phase to the CsCl phase of CdO occurs, respectively, at 76.12 and 65 GPa for the LDA and the GGA calculations. Our calculations are in good agreement with other first‐principles transition pressure range of 80–90 GPa and even with experimental results p t = 90.6 GPa.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…It is found that the static phase transition from the rocksalt phase to the CsCl phase of CdO occurs, respectively, at 76.12 and 65 GPa for the LDA and the GGA calculations. Our calculations are in good agreement with other first‐principles transition pressure range of 80–90 GPa and even with experimental results p t = 90.6 GPa.…”
Section: Resultssupporting
confidence: 91%
“…The phase transition from NaCl (B1)‐type to CsCl (B2)‐type was observed at pressure around 90.6 GPa . Total energy calculations in the framework of density functional theory predicted a B1–B2 phase transition at 89 , 85 , 83.1 , 86.6 , and 90.31 GPa . On the other hand, recent first‐principles pseudopotential calculations have addressed the mechanical stability of the rocksalt phase of CdO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent past years, several theoretical studies on pressure-dependent physical properties and elastic constants of CdO compound have also been published [4][5][6][7][8]. Peng et al [4,5] have studied the structural stability and the pressure-dependent elastic constants of both NaCl-type and CsCl-type phases using Plane-Wave PseudoPotential (PW-PP) method.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by this experiment, in this work we chose the interesting sodalite cage cluster Cd 12 O 12 as the building block to construct the possible metastable CdO polymorphs with promising application in photoelectronics. Moreover, the motivation of our work is also based on the fact that there are scarce studies about CdO polymorphs, especially about the low-density phases. …”
Section: Introductionmentioning
confidence: 99%